2014
DOI: 10.1364/oe.22.022831
|View full text |Cite
|
Sign up to set email alerts
|

On-chip generation and demultiplexing of quantum correlated photons using a silicon-silica monolithic photonic integration platform

Abstract: We demonstrate the generation and demultiplexing of quantum correlated photons on a monolithic photonic chip composed of silicon and silica-based waveguides. Photon pairs generated in a nonlinear silicon waveguide are successfully separated into two optical channels of an arrayed-waveguide grating fabricated on a silica-based waveguide platform.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…As it is very difficult to integrate interferometric bandpass filters on-chip, alternative solutions have to be found to provide spectral filtering. Matsuda et al have demonstrated the integration of an AWG and a nanowire on the same silicon chip [63]. As the AWG can only provide 30-dB isolation, off-chip bandpass filters and fiber Bragg gratings are still needed to achieve the overall > 100 dB isolation.…”
Section: On-chip Spectral Filtersmentioning
confidence: 99%
“…As it is very difficult to integrate interferometric bandpass filters on-chip, alternative solutions have to be found to provide spectral filtering. Matsuda et al have demonstrated the integration of an AWG and a nanowire on the same silicon chip [63]. As the AWG can only provide 30-dB isolation, off-chip bandpass filters and fiber Bragg gratings are still needed to achieve the overall > 100 dB isolation.…”
Section: On-chip Spectral Filtersmentioning
confidence: 99%
“…In order to evaluate the quality of the distributed entanglement and assess the effect of the various demultiplexers, we measure the following parameters: the visibility in the natural and the diagonal bases, V = (C max − C min )/(C max + C min ), where C max and C min are respectively the maximum and minimum number of coincidences when one of the polarisation basis angles is changed; the violation of the CHSH inequality, which is quantified by the Bell parameter S; and the brightness (21,27) 0.82 ± 0.04 0.77 ± 0.04 2.25 ± 0.07 216 0.20 0.970 ± 0.053 AWG (23,25) 0.77 ± 0.04 0.74 ± 0.05 2.10 ± 0.10 149 0.064 0.972 ± 0.059 AWG (22,26) 0.79 ± 0.05 0.66 ± 0.05 2.00 ± 0.10 116 0.079 0.906 ± 0.066 DGFT (23,25) 0.79 ± 0.05 0.82 ± 0.05 2.30 ± 0.10 108 0.030 1.000 ± 0.072 DGFT (22,26) 0 B. The results of our measurements are given in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the broad bandwidth of photon a) Electronic mail: isabelle.zaquine@telecom-paristech.fr pairs produced by spontaneous parametric down conversion can allow for entanglement distribution to multiple user pairs from a single source using wavelength division multiplexing techniques. This possibility has been explored in several recent works [22][23][24][25][26] , while further work is in progress to integrate these devices 27 and to design flexible optical networks based on such sources 28 . In view of the wide use of wavelength division multiplexing in quantum networks for practical applications, it is essential to be able to properly test the employed demultiplexing technologies and quantify their effect to the quality of the distributed entanglement 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrations of structures that enhance photon generation rates via SFWM include rectangular waveguides [50,[77][78][79], and microring resonators [38,41,43,[80][81][82][83][84][85][86][87][88]; see Figure 5D-F. As SFWM involves the annihilation of two photons, pair generation rates scale with the square of the optical intensity. With standard single-mode waveguide geometries of 500 nm by 220 nm, optical intensities in integrated structures are enhanced by the inverse of the effective mode area [70] with respect to bulk-silicon SFWM pair sources.…”
Section: Photonic Structuresmentioning
confidence: 99%